Transmission characteristics of Mach-Zehnder interferometer comb filter based on thermal operation - Islam, M. S. (2014)
We propose and experimentally demonstrate switchable and tunable transmission characteristics of a Mach-Zehnder interferometer comb filter based on thermal operation. Its temperature characteristics are investigated to reveal a shift in the peak wavelength position from 0.003 to 0.004 nm/A degrees C and a tunable range of wavelength spacing of 0.76-0.90 nm for maximum and minimum effective lengths, respectively. This configuration provides the unique advantages of an all-fiber structure, tunable wavelength spacing, switchable spectral peaks, independent tuning of the center wavelength and wavelength spacing of the spectral peaks, and low polarization sensitivity. It is relatively simple to fabricate and expected to have applications in temperature fiber optic sensors and multiwavelength fiber laser sources.